Circadian rhythm as a key player in cancer progression as well as a therapeutic target in HER2-positive advanced gastric cancer treatment - Wang, Shihao; Khan, Suliman; Nabi, Ghulam; Li, Hong-Yu (Frontiers in Oncology, 2023)
Gastric cancer is known as one of the most common cancer types with less than one1 year prognosis in metastatic disease, which poses a huge disease burden. One of the key players in poor prognosis is human epidermal growth factor receptor 2 (HER2), which also contributes to the pathogenesis of HER2-positive advanced gastric cancer. Trastuzumab is used as first-line chemotherapy that targets the expression of HER2, however, trastuzumab resistance is an inevitable major problem. To overcome this problem, readjustment of the circadian system may play a crucial role, as dysregulation in the expression of circadian clock genes has been observed in tumors. Therefore, for better efficacy of trastuzumab, pharmacological modulation of clock components can be considered for better efficacy of trastuzumab. In this review,Here, we discuss the association of circadian clock with cancer progression, development, and treatment.Metformin-based chronotherapy can disrupt BMAL1-CLOCK-PER1-HK2 axis, thereby affecting glycolysis oscillation to overcome trastuzumab resistance in HER2-positive advanced gastric cancer.